Improvement of Hemoglobin Levels in Pregnant Women with Anemia Through Dragon Fruit Consumption - Indrayani, Triana; Kurniati, Eni (Indonesian Journal of Global Health Research, 2024)
Anemia frequently manifests in pregnant women as a consequence of alterations in the cardiovascular system, leading to hemodilution and a subsequent decline in blood oxygen levels. The augmented iron demands during pregnancy arise from the needs of the fetus and placenta, coupled with physiological shifts like heightened blood volume and red blood cell count. This elevation in levels may contribute to diminished hemoglobin and hematocrit levels, consequently escalating the prevalence of anemia and iron deficiency during pregnancy. A viable solution for averting anemia in pregnant women involves the consumption of fruits rich in iron and vitamin C, such as dragon fruit, crucial for hemoglobin synthesis. The research method employed in this study followed a quantitative approach, specifically utilizing quasi-experimental research with a pretest-post-test design, including a control group. The study population comprised all pregnant women attending TPMB N Depok, West Java, during October-December 2023. Inclusion criteria involved pregnant women aged 16-34 weeks who visited TPMB N and exhibited signs of anemia. The study sample consisted of pregnant women willing to consume 200 cc of dragon fruit juice daily for a duration of 14 days. Bivariate data analysis was conducted using the Mann-Whitney Test. The intervention implemented involved administering dragon fruit juice, prepared by blending 200g of dragon fruit with 200cc of water and adding 3 tablespoons of sugar. The findings reveal a statistically significant difference in Hb levels among pregnant women before and after the consumption of dragon fruit juice, with a P value of 0.001.